Pemahaman dan Perspektif Mahasiswa Mengenai Manfaat Air Tebu (Saccharum officinarum) dalam Prospek Kesehatan - Tabitha Qotrunnada Sulistiyanto; Siti Merlianawati Sinaga; Ade Suryanda (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Sugarcane (Saccharum officinarum) is a plant that stores food reserves in the stem. Reserve food is in the form of water. Sugarcane water (Saccharum officinarum) can be consumed by humans. Sugarcane water (Saccharum officinarum) has many benefits, one of which is that it can lower cholesterol, control blood pressure, strengthen endurance, and much more. The purpose of this study was to determine the understanding and perspective of students regarding the benefits of sugarcane water (Saccharum officinarum) in health prospects. The type of research used is descriptive quantitative research with data collection techniques, namely the distribution of questionnaires through the help of the Google Form application. The results obtained are 92% of students already know about sugarcane plants and 96% of students think that sugarcane (Saccharum officinarum) is a plant that is rich in benefits. The conclusion of this study based on the results of the study showed that the understanding and perspective of students regarding the benefits of sugarcane water (Saccharum officinarum) in health prospects was classified as good.